Comparative Effect of Horse Dung and Pig Dung on The Early Growth of Nauclea diderrichii (De Wild) Seedlings - O.D. Ayeni; M.O. Ojo; B.O. Okumodi (Journal of Applied Sciences and Environmental Management, 2021)
The research work examined the effect of horse dung and pig dung on the early growth of Nauclea diderrichii seedling. The experiment was carried out at the back of library of Federal College of Forestry, Ibadan. The experiment consisted of five treatments which were replicated nine times in a completely Randomized design (CRD). The following materials were used: Topsoil, Polythenepot, seeds of Nauclea diderrichii, Horse dung and pig dung, sieve, wheel barrow, venier caliper, ruler, field record book and pen. Data on the number of stem girth, height, leave production and leave area were recorded fortnightly starting from a week after transplanting. The data collected were analyzed through Analysis of Variance (ANOVA). The result revealed that 15g of horse dung + 2kg of top soil had the  highest mean number of height value of 12.49cm followed by 10kg of horse dung +2kg of topsoil,(10.15cm). While topsoil only had the least mean number of height (8.25cm). The result further showed the highest mean stem girth (0.30cm) followed by 0.27cm and produced least mean stem girth of 0.24cm in treatments T12, T1 and T5 respectively. Also, in the leaf production the result revealed that 15g of horse dung +2kg of topsoil had the highest mean number of 16.69cm followed by treatment one 12,56cm and topsoil only produce the least mean leaf production of 9.40cm. The result further showed highest mean leave area (134.50cm2 ) followed by treatment one 124.60cm2 and (T5) produced the least mean leaf area of 108.06cm2. Analysis of variance (ANOVA) for plant height, stem girth, leaf production and leaf area also indicated that the treatment applied Nauclea diderrichii seedlings showed no significant effect. Generally 15g of horse dung + 2kg of topsoil produced the best result in terms of plant height, stem girth, leaf production and leave area of Nuclea diderrichii seedlings, hence treatment two (T2) is best suitable for raising Nuclea diderrichii seedlings.